Association Between Sugar-Sweetened Beverage Intake and Proxies of Acculturation Among U.S. Hispanic and Non-Hispanic White Adults. Issue 5 (May 2016) - Park, Sohyun; Blanck, Heidi M.; Dooyema, Carrie A.; Ayala, Guadalupe X.
Purpose: This study examined associations between sugar-sweetened beverage (SSB) intake and acculturation among a sample representing civilian noninstitutionalized U.S. adults. Design: Quantitative, cross-sectional study. Setting: National. Subjects: The 2010 National Health Interview Survey data for 17, 142 Hispanics and U.S.-born non-Hispanic whites (≥18 years). Measures: The outcome variable was daily SSB intake (nondiet soda, fruit drinks, sports drinks, energy drinks, and sweetened coffee/tea drinks). Exposure variables were Hispanic ethnicity and proxies of acculturation (language of interview, birthplace, and years living in the United States). Analysis: We used multivariate logistic regression to estimate adjusted odds ratios (ORs) for the exposure variables associated with drinking SSB ≥1 time/d after controlling for covariates. Results: The adjusted odds of drinking SSB ≥1 time/d was significantly higher among Hispanics who completed the interview in Spanish (OR = 1.65) than U.S.-born non-Hispanic whites. Compared with those who lived in the United States for <5 years, the adjusted odds of drinking SSB ≥1 time/d was higher among adults who lived in the United States for 5 to <10 years (OR = 2.72), those who lived in the United States for 10 to <15 years (OR = 2.90), and those who lived in the United States for ≥15 years (OR = 2.41). However, birthplace was not associated with daily SSB intake. Conclusion: The acculturation process is complex and these findings contribute to identifying important subpopulations that may benefit from targeted intervention to reduce SSB intake.